Analisis Penggunaan Base Isolation System Tipe Lrb Pada Bangunan Gedung Rsud Kabupaten Lombok Barat (Analysis Of Lrb Type Base Isolation Systems In Building Rsud Kabupaten Lombok Barat) - Lalu Ibrohim Burhan; Ni Nyoman Kencanawati; Buan Anshari (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2023)
The hospital is a very vital building that functions as a public service both under normal conditions and during a disaster. In (SNI 1726-2012) for buildings with IV risk, it is recommended to use a base isolation system. The use of the base isolation system is able to minimize the earthquake forces received by the building structure. This journal will review the elastomeric isolation system. The mechanism of action of elastomeric rubber is to use rubber with steel plates inside. The use of rubber is to reduce earthquake vibrations, while steel plates are used to increase the stiffness of the rubber cushions so that the deflection and deformation of the building when resting on the rubber cushions are not large. This study was conducted to examine the effect of using base isolators when compared to buildings without them (fixed base structures). From the results of the study, it was concluded that the use of base isolators increased the natural period of the structure from 0.941 seconds for fix base to 1.456 seconds for LRB so as to reduce story drift in buildings